Effect of Abnormal Savda Munziq on Hypertrophic Scar Formation in A Rabbit Ear Model - 王虎军 高伟成 马少林 (Chinese journal of integrative medicine, 2015)
Objective： To investigate whether administrating Abnormal Savda Munziq （ASMq）, a traditional Uighur herbal preparation used for the prevention or treatment of diseases, affects hypertrophic scar （HTS） formation by using an established rabbit ear model. Methods： The HTS rabbit model was created by circular full- thickness skin excisions on both ears of rabbits. Twenty rabbits were randomized into four groups, with 5 rabbits and 60 wounds in each group. Group A was the control group, treated with normal saline daily. Groups B, C, and D were the treatment groups at three different doses of ASMq （400, 800, and 1200 mg/kg body weight, respectively, daily, by gastrogavage）. Twenty wounds were randomly chosen from each group on the 40th day after treatment and specimen were examined. Scar elevation index （SEI） was analyzed with histological assessment, and ultrastructure analysis was analyzed with a transmission electron microscopy. Results： Groups B, C, and D demonstrated significant reductions in SEI as compared with the control group at 35.9% （P=0.0212）, 48.2% （P=0.0108）, and 52.7% （P=0.0103）, respectively in a dose-response manner. SEI was lowered in Group D compared with Group B with a significant difference （P=0.015）. However, there were no significant differences between Groups B and C, or between Groups C and D. Histological analysis showed that high- dose ASMq （1200 mg/kg） could enhance the softening of HTS of rabbit ears and increase the compliance as shown in general. Ultrastructure analysis showed that with increased ASMq dose, the fibroblasts, pro-collagen, collagen, endoplasmic reticulum and ribosomes were reduced gradually. Conclusions： Orally administered ASMq significantly reduces the severity of HTS in the rabbit ear model. The findings of this study may have clinical implications on the management of human HTS.